ATBS1-INTERACTING FACTOR 2 negatively regulates dark- and brassinosteroid-induced leaf senescence through interactions with INDUCER OF CBF EXPRESSION 1. (30th November 2019) - Kim, Yoon; Park, Seon-U; Shin, Dong-Min; Pham, Giang; Jeong, You Seung; Kim, Soo-Hwan
Abstract: ATBS1-INTERACTING FACTOR 2 (AIF2) is a non-DNA-binding basic helix–loop–helix (bHLH) transcription factor. We demonstrated that AIF2 retards dark-triggered and brassinosteroid (BR)-induced leaf senescence in Arabidopsis thaliana . Dark-triggered BR synthesis and the subsequent activation of BRASSINAZOLE RESISTANT 1 (BZR1), a BR signaling positive regulator, result in BZR1 binding to the AIF2 promoter in a dark-dependent manner, reducing AIF2 transcript levels and accelerating senescence. BR-induced down-regulation of AIF2 protein stability partly contributes to the progression of dark-induced leaf senescence. Furthermore, AIF2 interacts with INDUCER OF CBF EXPRESSION 1 (ICE1) via their C-termini. Formation of the AIF2–ICE1 complex and subsequent up-regulation of C-REPEAT BINDING FACTOR s ( CBF s) negatively regulates dark-triggered, BR-induced leaf senescence. This involves antagonistic down-regulation of PHYTOCHROME INTERACTING FACTOR 4 ( PIF4 ), modulated through AIF2-dependent inhibition of ICE1's binding to the promoter. PIF4-dependent activities respond to dark-induced early senescence and may promote BR synthesis and BZR1 activation to suppress AIF2 and accelerate dark-induced senescence. Taken together, these findings suggest a coordination of AIF2 and ICE1 functions in maintaining stay-green traits. Abstract : AIF2–ICE1 transcriptional complex is negatively involved in dark-triggered and brassinosteroid-induced leaf senescence, maintaining plant growth and enabling them to stay green longer.